2017
DOI: 10.1158/1055-9965.epi-17-0660
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient–Provider Race, Ethnicity, and Gender Concordance on Cancer Screening: Findings from Medical Expenditure Panel Survey

Abstract: Racial and ethnic minorities experience lower rates of cancer screening compared with non-Hispanic whites (NHWs). Previous studies evaluating the role of patient-provider race, ethnicity, or gender concordance in cancer screening have been inconclusive. In a cross-sectional analysis using the Medical Expenditure Panel Survey (MEPS), data from 2003 to 2010 were assessed for associations between patient-provider race, ethnicity, and/or gender concordance and, screening (American Cancer Society guidelines) for br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 43 publications
(43 reference statements)
1
59
1
Order By: Relevance
“…Our study showed that concordance between urologist sex and sex of the patient increased radical cystectomy utilization between female patients seen by female urologists. This finding serves as a potential opportunity to improve the utilization of radical cystectomy in line with prior studies that have shown that gender concordance between providers and patients can improve clinical outcomes [27] . Despite a significant proportion of women receiving a radical cystectomy, there was a dearth of female urologists, which might in part explain the overall underutilization of radical cystectomy.…”
Section: Discussionsupporting
confidence: 75%
“…Our study showed that concordance between urologist sex and sex of the patient increased radical cystectomy utilization between female patients seen by female urologists. This finding serves as a potential opportunity to improve the utilization of radical cystectomy in line with prior studies that have shown that gender concordance between providers and patients can improve clinical outcomes [27] . Despite a significant proportion of women receiving a radical cystectomy, there was a dearth of female urologists, which might in part explain the overall underutilization of radical cystectomy.…”
Section: Discussionsupporting
confidence: 75%
“…However, distressingly, in the absence of gender concordance between advocates and those they advocate for-particularly in instances where men are advocating for women-women have been found to fare worse than their male counterparts, facing disadvantages in terms of pay equality (1), ascension to leadership positions (2), educational outcomes (3), legal dispute resolution (4), and even medical treatment (5). In the medical setting, research suggests that gender discordance may yield lower rapport and patient satisfaction (6), reduced adherence to preventative care protocols (7), and weaker patient-physician communication (8).…”
mentioning
confidence: 99%
“…The screening and treatment of precancerous lesions at recommended intervals can prevent cervical cancer, and specific recommendations have been issued for HIV‐infected women for cytological screening with the addition of HPV testing . Higher cervical cancer rates suggest that HIV‐infected Hispanic women may be receiving inadequate screening services, similarly to what has been observed in the general population, although there is little information on screening rates specific to this group. Barriers to screening among HIV‐infected women may include a fear of disclosing their HIV status to providers, a lack of centralized clinical services, and preferential attention to other aspects of HIV care .…”
Section: Discussionmentioning
confidence: 94%